Harmonized Commodity Description and Coding System : explanatory notes (The Organization BrusselsBE, 2012)
Contains the official text of the explanatory notes to the Harmonized Commodity Description and Coding System, including the Subheading explanatory notes indicating the scope and content of certain of the harmonized system subheadings.
Contents: v. 1: Sections 1- VI, ch. 1 - 28. - v. 2: Sections VI - VIII, ch. 29 - 43. - v.3: Sections IX - XIII, ch 44 - 70. - v. 4: Sections XIV - XVI, ch. 71-84. - v. 5: Sections XVI - XXI, ch. 85 - 97. On permanent loan to Single Market and Economy Sub-Programme (Mr. Breedy, Mr. Black, Mr. Watson).